2014
DOI: 10.3384/ecp14096727
|View full text |Cite
|
Sign up to set email alerts
|

The Modelica BehaviorTrees Library: Mission Planning in Continuous-Time for Unmanned Aircraft

Abstract: The paper introduces a continuous-time architecture and a Modelica library for mission planning based on behavior trees. It allows to study the long-time behavior of complex aircraft models in interaction with reactive mission plans by means of efficient simulations. The developed Modelica library is used in a mission example for a solar high-altitude aircraft and the advantages of the behavior tree formulation in both simulation speed and modularity are discussed. The architecture will further be used to depl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…BTs have also been studied in machine learning applications [7], [8] and details regarding efficient parameter passing was investigated in [9]. Finally, a Modellica implementation of BTs was presented in [18].…”
Section: Introductionmentioning
confidence: 99%
“…BTs have also been studied in machine learning applications [7], [8] and details regarding efficient parameter passing was investigated in [9]. Finally, a Modellica implementation of BTs was presented in [18].…”
Section: Introductionmentioning
confidence: 99%
“…One of the recent topics in this area is asynchronous (or event-driven) BT, which are deviant from classical synchronous BT formulation. It was shown that asynchronous BT outperforms synchronous in continuous-time mission simulation [10]. Being flexible and reactive, behavior trees frequently require sort of inner memory, e.g., for a way-point missions.…”
Section: Introductionmentioning
confidence: 99%
“…1: Simple tasks can be connected hierarchically in a behavior tree in order to describe the energy harvesting strategy of a solar-powered aircraft. See [7].…”
Section: Behavior Treesmentioning
confidence: 99%
“…The behavior tree is built using the Modelica BehaviorTrees library [7]. The library provides a generic framework to graphically compose behavior trees (see Fig.…”
Section: Behavior Trees In Mission Managementmentioning
confidence: 99%
See 1 more Smart Citation